THE USE OF WORD HUNTS TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Wahyuningtyas, Annisa (UNIVERSITAS SLAMET RIYADI, 2017)
ABSTRACTVocabulary is essential component of all use of language. When the students acquaint new vocabulary, they must know the meaning of words. They must also know how to arrange individual words within the sentence. Vocabulary helps the students to express their ideas fluently and effectively. The aims of this study were to know whether Word Hunts can improve students vocabulary mastery and to find out how Words Hunts improve the vocabulary mastery of the eighth grade students of SMP N 1 Mojogedang in 2017/2018 Academic Year. This study was conducted at the eleventh grade of SMPN 1 Mojogedang. The method of the study was classroom action research which was conducted from November 2017 until January 2018. The data were collected through test (oral test) and non-test (observation, interview, and documentation). While, to analyze the data was used t-test. The result of this study showed that the implementation of Word Hunts was succsessful to improve the students‟ vocabulary mastery. The mean score increased from 52.09 in pre-test became 75.55 in post-test 1 and became 86.61 in post-test 2. It can be concluded that Word Hunts was appropriate to improve the students‟ vocabulary mastery in teaching and learning process. Moreover, the class condition were more attractive and more fun during teaching and learning process. Keywords: Word Hunts, Classroom Action Research, Vocabulary Mastery. ABSTRAKKosakata adalah komponen penting dari semua penggunaan bahasa. Ketika siswa memperkenalkan kosa kata baru, mereka harus tahu arti kata-kata. Mereka juga harus tahu bagaimana mengatur kata-kata individual dalam kalimat. Kosakata membantu siswa untuk mengekspresikan ide-ide mereka dengan lancar dan efektif. Tujuan dari penelitian ini adalah untuk mengetahui apakah Word Hunts dapat meningkatkan penguasaan kosakata siswa dan untuk mengetahui bagaimana Words Hunts meningkatkan penguasaan kosakata siswa kelas delapan SMP N 1 Mojogedang pada Tahun Akademik 2017/2018. Penelitian ini dilakukan di kelas XI SMPN 1 Mojogedang. Metode penelitian ini adalah penelitian tindakan kelas yang dilakukan dari November 2017 hingga Januari 2018. Data dikumpulkan melalui tes (tes lisan) dan non-tes (observasi, wawancara, dan dokumentasi). Sedangkan untuk menganalisis data digunakan uji-t. Hasil penelitian ini menunjukkan bahwa penerapan Word Hunts berhasil meningkatkan penguasaan kosakata siswa. Skor rata-rata meningkat dari 52,09 pada pre-test menjadi 75,55 pada post-test 1 dan menjadi 86,61 pada post-test 2. Dapat disimpulkan bahwa Word Hunts tepat untuk meningkatkan penguasaan kosakata siswa dalam proses belajar mengajar. Selain itu, kondisi kelas lebih menarik dan lebih menyenangkan selama proses belajar mengajar. Kata kunci: Perburuan Kata, Penelitian Tindakan Kelas, Penguasaan Kosakata.